1994
DOI: 10.1159/000109546
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metallothionein in Stress

Abstract: Brain metallothionein (MT) levels have been measured in the rat brain in basal and stress situations with polyclonal antibodies which do not cross-react significantly with the brain-specific MT isoform growth inhibitory factor (MT-III). Acute immobilization stress increases MT levels in most but not all brain areas. In contrast, chronic immobilization stress has no effect on MT levels. Although glucocorticoids and monoamines appear to have a role in brain MT regulation in control rats, they do not appear to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In vitro studies have also shown that astrocytes synthesize metallothioneins when exposed to cytokines and transitional metal ions [6,14,181. Current information about the cellular distribution of metallothionein in the CNS is limited to physiological changes [2,11,161 and little detailed information is available for reactive astrocytes in the human brain although metallothionein positive astrocytes have been described in Alzheimer's disease [15].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have also shown that astrocytes synthesize metallothioneins when exposed to cytokines and transitional metal ions [6,14,181. Current information about the cellular distribution of metallothionein in the CNS is limited to physiological changes [2,11,161 and little detailed information is available for reactive astrocytes in the human brain although metallothionein positive astrocytes have been described in Alzheimer's disease [15].…”
Section: Introductionmentioning
confidence: 99%
“…Certainly this is surprising given the known positive effect of glucocorticoids on the MT-I+II genes. Possible explanations have been dis cussed previously [16,29,34], and more work is in pro gress to add further insight into this paradoxical result. This is the first time that the effect of stress on brain MT-III has been evaluated.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, slight increases were seen after 3 h of stress in hypothalamus, cerebellum and remaining brain (except hippocampus), which returned to basal levels after 8 h of stress. The small, transient increases of MT-I mRNA levels should, presumably, account for the small increases of the protein levels induced by stress [14,15,29], A more puzzling result is that obtained in the hippo campus, where a significant decrease of MT-I mRNA lev els was observed 3 h after the onset of stress, which returned to normal 5 h later (8 h of stress). This brain area is one where the effect of stress on MT-I+1I protein levels is not consistent through experiments, increasing them only occasionally [29], The transient decrease of MT-I mRNA levels could be related to such inconsistency, but more work is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MT-1 was not one of these proteins, MT-3 could indirectly be an MT-1 regulator; on the basis of our results we are unable to declare a direct or indirect role of MT-3 in MT-1 regulation. Moreover, it is noticed that MT-1 and MT-2 genes are co-ordinately regulated in mice by metals and hormones such as glucocorticoids (Hidalgo et al, 1994b;Searle et al, 1984;Yagle and Palmiter, 1985) among other regulators. Since our results showed lower levels of corticosterone at basal conditions in Mt-3 KO mice, this may be one of the possible factors that could explain this decreased MT-I expression in the absence of MT-3.…”
Section: Discussionmentioning
confidence: 99%